Optimization days for Black Soldier Fly (BSF) to be matured and escape from chicken dung based on environmental factors - Hamidon, Nuramidah; Ahmad Shahabuddin, Ainie Najwa; Hashim, Nor Haslina; Awang, Zarizi; Muhamad, Mimi Suliza; Mohd Sunar, Norshuhaila; Abd Hamid, Nor Hazren; Harun, Hasnida; Ali, Roslinda; Awang, Mariah; Abdul Rahman, Muhammad Ashraf (Penerbit UTHM, 2020)
Hermetia illucens, the Black Soldier Fly, belongs to the diptera Stratiomyidae family. The black soldier fly is interesting because it can be used to solve many of the problems associated with large accumulations of manure during confined feeding operations [1]. Although not known as a disease vector, adult soldier flies are a potential mechanical vector of different pathogenic agents. Accidental ingestion of black soldier fly larvae by animals or humans would be more likely a negative interaction. Black soldier fly is often associated with animals and plant, usually around decaying organic materials such as animal waste or plant material. Since black soldiers fly larvae consume decaying matter, they were used in commercial swine and poultry facilities to reduce animal manure. BSF adults are usually found near places where there is an abundance of manure, decaying food or dead animals. Smells from decaying organic matter attract women ready to lay egg while male prefer sunny spots where vegetation prevail. Black soldier fly is regarded as a beneficial insect in confined animal installations because its tendency to colonize animal waste. Due to the rapid growth of the world population, which is predicted to reach 9 billion people by 2050, global food demand will increase by nearly 100% from 2005 to 2050, while animal feed and human food production are expected to increase by 60 percent through agriculture [1]. Biotic factors can affect the performance of BSF as well. Larval density, for example, can be a major factor affecting development rates [2]. In addition, high larval densities can reduce the quality of the substrate by accumulating larval waste products and direct energy costs can be generated if larvae spend extra energy interacting with each other.